2019
DOI: 10.1136/rapm-2019-100658
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral nerve blocks and postoperative pain outcomes after mastectomy: a meta-analysis of randomized controlled trials

Abstract: Background and objectivesSeveral studies have evaluated the effect of pectoral nerve blocks to improve postoperative analgesia following breast cancer surgery resulting in contradictory findings. The aim of this study was to examine the effect of Pecs blocks on postoperative analgesia in women following mastectomies.MethodsWe performed a quantitative systematic review in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Articles of randomized controlled trials th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 37 publications
4
25
0
1
Order By: Relevance
“…The random effect model has an advantage to the fixed effect model since it does not rely on the assumption that a true effect size is the same in all combined studies [11]. Publication bias was evaluated by examining for asymmetric funnel plot using the Egger's regression test [12,13]. A one-sided P < 0.05 was considered as an indication of an asymmetric funnel plot.…”
Section: Meta-analysesmentioning
confidence: 99%
“…The random effect model has an advantage to the fixed effect model since it does not rely on the assumption that a true effect size is the same in all combined studies [11]. Publication bias was evaluated by examining for asymmetric funnel plot using the Egger's regression test [12,13]. A one-sided P < 0.05 was considered as an indication of an asymmetric funnel plot.…”
Section: Meta-analysesmentioning
confidence: 99%
“…A large variety of regional anesthesia techniques have been commonly used to minimize postoperative pain [4][5][6]. In addition, several techniques (e.g., transverse abdominis plane blocks, pectoral nerve blocks, brachial plexus blocks) have been evaluated in quantitative systematic reviews [7][8][9]. These techniques have emerged as effective non-opioid strategies to reduce post-surgical pain.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques were evaluated such as transverse abdominis plane (TAP) blocks, pectoral nerve blocks, and brachial plexus block. [1][2][3][4] Erector spinae plane (ESP) block was first described by Forero et al 5 It is an interfacial plane block used for the treatment of thoracic neuropathic pain. It consists in the injection of a local anesthetic (LA) into the fascial plane situated between the erector spinae muscle and the transverse process of the vertebra.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with high level of evidence confirmed that ESP block could be an effective procedure to improve postoperative analgesia after digestive surgery. 3,6,7 However, in these studies various surgical procedures with anatomical differences were included, which cause significant heterogeneity among the studies. As far as we know, there has been no quantitative systematic review which evaluated the efficacy of ESP block in the management of postoperative pain in a specific laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%